2000
DOI: 10.1046/j.1432-1327.2000.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro folding, purification and characterization of Escherichia coli outer membrane protease OmpT

Abstract: OmpT is a protease present in the outer membrane of Escherichia coli. The enzyme was overexpressed without its signal sequence in E. coli using a T7 system, resulting in the accumulation of OmpT as inclusion bodies. After solubilization of the inclusion bodies in urea, the protein could be folded in vitro by dilution in the presence of detergent n-dodecyl-N,N-dimethyl-1-ammonio-3-propanesulphonate. The addition of lipopolysaccharide to the protein was essential to obtain active enzyme. The correctly folded pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
189
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(209 citation statements)
references
References 37 publications
19
189
1
Order By: Relevance
“…7 and Table 2) that emphasize the importance of the water content to the interpretation of the spectra. Besides the dominant b-sheet structure in accordance with the study by Kramer et al (2000) applying CD spectroscopy, a-helical structures were also observed, which seemed to be expressed most strongly at higher water content (Table 1), but are reduced in the presence of lipids. These data seem to be in contradiction to Vandeputte-Rutten et al (2001), who found b-sheet structures for crystallized OmpT 69% , but no a-helical structures (see also Protein Data Bank, no.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…7 and Table 2) that emphasize the importance of the water content to the interpretation of the spectra. Besides the dominant b-sheet structure in accordance with the study by Kramer et al (2000) applying CD spectroscopy, a-helical structures were also observed, which seemed to be expressed most strongly at higher water content (Table 1), but are reduced in the presence of lipids. These data seem to be in contradiction to Vandeputte-Rutten et al (2001), who found b-sheet structures for crystallized OmpT 69% , but no a-helical structures (see also Protein Data Bank, no.…”
Section: Discussionsupporting
confidence: 79%
“…OmpT was recombinantly expressed in E. coli and purified from inclusion bodies as described previously (Kramer et al 2000(Kramer et al , 2002 with some modifications.…”
Section: Omptmentioning
confidence: 99%
See 1 more Smart Citation
“…The internally quenched £uorogenic substrate Abz-Ala-Arg-Arg-Ala-Dap(dnp)-Gly was used in a £uorimetric activity assay, as described previously [4]. Assay conditions were 5 WM substrate, 1 mM Tween 20, 5 mM EDTA, 10 mM Tris, pH 8.3.…”
Section: Enzymatic Activity Assaysmentioning
confidence: 99%
“…The active site is located within a deep groove formed by loops L4 and L5 on the one side and L1, L2, and L3 on the other. The structure also reveals a binding site for a single lipopolysaccharide molecule that appears to be important for the catalytic activity of the enzyme (14,15,16). The finding that peptide hydrolysis is weakly inhibited by certain serine protease inhibitors was the basis for the classification of OmpT and its homologues as a distinct serine protease family.…”
mentioning
confidence: 97%